Контроль органів виконавчої влади за діяльністю правоохоронних органів в Україні - Музичук, О. М.; Muzychuk, O. M.; ORCID: http://orcid.org/0000-0001-8367-2504 (Право і безпека. – 2014. – № 2 (53). – С. 53-56, 2014)
Сформульовано поняття та визначено особливості контролю органів виконавчої влади за діяльністю правоохоронних органів в Україні. Зроблено висновок, що особливість контролю органів виконавчої влади за діяльністю правоохоронних органів в Україні полягає у тому, що правоохоронні органи, які, крім органів прокуратури, є органами виконавчої влади, одночасно можуть бути його суб’єктами та об’єктами, оскільки наділені повноваженнями взаємного контролю один щодо одного. Контроль органів виконавчої влади за діяльністю правоохоронних органів в Україні запропоновано визначити як комплексний, найбільш оперативний та об’ємний за предметом підвид державного контролю, здійснюваний урядом, центральними і місцевими органами виконавчої влади та спрямований на перевірку дотримання (виконання) правоохоронними органами законодавства з питань, що належать до їх компетенції.

The notion of control by the executive authorities over law enforcement agencies’ activity in Ukraine is formulated and its features are determined. It is noted that it is necessary to distinguish such concepts as «subjects of the state control» and «subjects of control in the state», where the latter is broader in content, as it involves not only state, but also self-governing, public and international subjects. Special attention is paid to the fact that referring those subjects not having the status of the state (for example, local governments) to the subjects of the state control is the most common mistake both in the current legislation and scientific literature. And vice versa there are some facts of not referring all public bodies to the subjects of the state control, for example, local administrations. It is noted that the state control is often considered as a synonym of the terms «control in the state administration», «civilian control», «control of the executive authorities», that is also not grounded because the state control is a kind of control in the state administration and civilian control, and control of the executive authorities is only one of its subspecies, which most clearly indicate its function and features in the state. It is concluded that the feature of control by executive authorities over law enforcement agencies in Ukraine is that law enforcement agencies except prosecutor’s office is the executive bodies and can be simultaneously its subjects and objects as they are empowered with mutual control over each other. Control by the executive authorities over law enforcement agencies in Ukraine is offered to define as a complex, the most efficient and surround by the subject subspecies of the state control, exercised by the government, central and local authorities of executive power and directed on verifying the compliance (realization) legislation by law enforcement agencies within their competence.

Сформулировано понятие и определены особенности контроля органов исполнительной власти за деятельностью правоохранительных органов в Украине. Сделан вывод, что особенность контроля органов исполнительной власти за деятельностью правоохранительных органов в Украине заключается в том, что правоохранительные органы, которые, кроме органов прокуратуры, являются органами исполнительной власти, одновременно могут быть его субъектами и объектами, поскольку наделены полномочиями взаимного контроля. Контроль органов исполнительной власти за деятельностью правоохранительных органов в Украине предложено определить как комплексный, наиболее оперативный и объёмный по предмету подвид государственного контроля, осуществляемый правительством, центральными и местными органами исполнительной власти и направленный на проверку соблюдения (исполнения) правоохранительными органами законодательства по вопросам, относящимся к их компетенции.
Control by the executive authorities over law enforcement agencies in Ukraine
Контроль органов исполнительной власти за деятельностью правоохранительных органов в Украине
Музичук, О. М. Контроль органів виконавчої влади за діяльністю правоохоронних органів в Україні / О. М. Музичук // Право і безпека. – 2014. – № 2 (53). – С. 53-56.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; правоохоронні органи; правоохранительные органы; law enforcement agencies; органи виконавчої влади; органы исполнительной власти; executive authorities; контроль; control; державний контроль; государственный контроль; state control